INDEPENDENSI DEWAN PENGAWAS SYARIAH SEBAGAI PENGAWAS KEPATUHAN SYARIAH DI LEMBAGA KEUAGAN SYARIAH - R. Suhaimi (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2020)
Introduction: The sharia supervisory board is an independent institution in a sharia financial institution, the existence of DPS is as a supervisory agency for the implementation of sharia compliance in sharia financial institutions, the appointment of DPS in LKS is through the general meeting of shareholders or RAT which has been approved by he national sharia board (DSN), the sharia supervisory board can also be proposed by the directors and by the highest shareholder of the LKS. Methods: This study uses a qualitative model that is literature study, qualitative research is a method that emphasizes the deeper aspects of understanding a problem rather than seeing a problem. Results: The sharia supervisory board as a supervisor in the Islamic financial institution as well as the long arm of the DSN has a role in ensuring the implementation of sharia compliance in LKS, however the appointment and dismissal of DPS is carried by the RUPS or RAT and can also be proposed by some of the strongest directors and shareholders in this institution and the provision of salaries provided by the LKS under supervision indicate that DPS will be less independent, this will raise suspicions that the appointment of DPS is in accordance with interests of big people in the LKS Conclusion and suggestion: The Sharia supervisory board is an independent institution whitin the LKS and supervises all business activities carried out by the LKS in the field of sharia compliance. The sharia supervisory board (DPS) is an extension of the national sharia council (DSN) which is assigned and authorized to serve all operations and sharia financing products. This research is still less than perfect in this study the data used is only based on secondary data obtained from several available sources such as journals, books and others, further research is expected to also use primary data through direct interviews with data sources which will provide reliable data. more accurate to research. Keywords: The sharia supervisory board, sharia compliance, Islamic financial institutions